Status preference, wealth, and dynamics in the open economy - Walter H. Fisher (Institute for Advanced Studies (IHS), 2001)
The implications of status preference in a simple open economy model will be investigated in this paper. The open economy is modeled as a continuum of identical representative agents who have preferences over consumption and status. In the paper status is identified as relative wealth, which takes the form of relative holdings international financial assets. A symmetric macroeconomic equilibrium is derived in which status is the source of transitional dynamics for consumption and the current account balance. This result illustrates another way to generate transitional dynamics in the small open economy model, which, as is wellknown, does not have well-defined dynamics under perfect capital mobility. The role of status plays in influencing the open economy's adjustment to various macroeconomic shocks is also considered.
Keywords: E21; F41; 330; status-preference; open economy dynamics; Sozialer Status; Offene Volkswirtschaft; Theorie